A case of falsely elevated D-dimer result - HAKLAR, GONCAGÜL; ŞİRİKÇİ, ÖNDER (My University, 2022)
Objectives Heterophile antibodies can cause interferences in immunometric assays. While many tests are shown to be affected by interference from heterophilic antibodies, the D-dimer test has rarely been reported to be affected. With this case, we report an elevated D-dimer measurement which was not compatible with the clinical presentation. Case presentation A 41-year-old patient who was admitted to hospital with heart palpitations had a D-dimer elevation irrelevant to his clinical condition. D-dimer measurements were repeated in new samples directly and after being treated in heterophilic blocking tube with two different reagent lots of a latex-based automated immunoturbidimetric assay and an immunoturbidometric assay. D-dimer values were normalized (0-0.5 mg/L) when we used a new lot of reagent on the same instrument or measured by an immunoturbidometric method on the chemistry analyzer. After treatment with HBT, all samples revealed D-dimer results within the reference ranges. Conclusions The presence of heterophile antibodies in a sample should be considered when an elevated D-dimer value that is not compatible with the clinical presentation is encountered. Apart from the patient\"s HA\"s causing false results, sporadic susceptibility of the reagents should also be kept in mind as a possibility.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); İlaç Keşfi; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology